Achievement Motivation of the High School Students: A Case Study among Different Communities of Goalpara District of Assam - Sarangi, C. (INDIAN EDUCATIONAL REVIEW, 2014)
The study examines the effect of achievement motivation on the academic achievement of high school students of tribal and nontribal communities vis-à-vis their sex and locale. The data were collected through descriptive survey method by adopting stratified random sampling technique. Gopal Rao’s Achievement Motivation Scale was used as a measure for the study and t’ test and Pearson’s co-efficient of correlation (r) were adopted to measure the significant difference and significant relationship between the variables. Consequently the study found no significant difference between tribal and non tribal and between male and female students. However, the urban students showed higher achievement motivation than the rural students of both the communities. In case of relationship, no significant relation was observed between achievement motivation and academic achievement of tribal, male and rural students. But a significant relationship was found between the achievement motivation and academic achievement of non tribal, female and urban students of both the communities.